2019
DOI: 10.3389/fgene.2019.00939
|View full text |Cite
|
Sign up to set email alerts
|

EBV-miR-BART7-3p Imposes Stemness in Nasopharyngeal Carcinoma Cells by Suppressing SMAD7

Abstract: Cancer stem-like cells, possessing “stemness” properties, play crucial roles in progression, metastasis, and drug resistance in various cancers. Viral microRNAs (such as EBV-miR-BART7-3p), as exogenous regulators, have been discovered to regulate malignant progression of nasopharyngeal carcinoma (NPC), suggesting a possible role of viral microRNAs in imposing stemness. In this study, we found that EBV-miR-BART7-3p induce stemness of NPC cells. We firstly reported that EBV-miR-BART7-3p increased the percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 42 publications
2
22
0
Order By: Relevance
“… 15 Numbers of studies have shown that NPC is closely associated with EBV infection. 16 , 17 , 18 , 19 It was found that EBV-coded miRNAs, such as EBV-miR-BART1, 20 BART2-5p, 21 BART7, 22 and BART13, 23 are involved in tumorigenesis and NPC progression, and could be used as biomarkers or prognostic indicators. In a prior study, we found that EBV-miR-BART22 has a high expression level in NPC.…”
Section: Introductionmentioning
confidence: 99%
“… 15 Numbers of studies have shown that NPC is closely associated with EBV infection. 16 , 17 , 18 , 19 It was found that EBV-coded miRNAs, such as EBV-miR-BART1, 20 BART2-5p, 21 BART7, 22 and BART13, 23 are involved in tumorigenesis and NPC progression, and could be used as biomarkers or prognostic indicators. In a prior study, we found that EBV-miR-BART22 has a high expression level in NPC.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these reports, both EBV-miR-BART1, and EBV-miR-BART7-3p have been shown to induce tumor metastasis by regulating various kinds of pathways in NPC [7,15]. We further discovered that EBV-miR-BART7-3p increased the chemoresistance of NPC [16]. With the development of the research of BARTs, we began to explore the bridge between the treatment of resistance and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…miR-BART7-3p has been hypothesized to play a role in tumor growth and invasion through the suppression of phosphatase and tensin homolog (PTEN) protein and others against decapentaplegic homolog 7 (SMAD7) [57,58]. PTEN is one of the main tumor suppressor genes involved in the regulation of the cell cycle.…”
Section: Bart Mirnas In Gastric Cancermentioning
confidence: 99%